Sistem Pendukung Keputusan Penerimaan Analis Di Pusat Penelitian Kelapa Sawit Menggunakan Metode Complex Proportional Assessment (Copras) - Nurliadi; Abdul Karim (AMIK STIEKOM SUMATERA UTARA, 2023)
Acceptance of analysts at the Palm Oil Research Center is an important process that requires the right decision. In this context, Decision Support Systems (DSS) can be used to assist decision making using the Complex Proportional Assessment (COPRAS) method. The COPRAS method is an effective method for making multi-criteria decisions. In this research, we apply the COPRAS method in SPK for analyst recruitment at the Palm Oil Research Center. The steps taken include identifying criteria, determining criteria weights, evaluating alternatives, normalization and aggregation, as well as ranking and selecting candidate analysts. The criteria considered in this research include educational qualifications, work experience, skills and competencies, communication skills, as well as motivation and personality. Each criterion is given a weight to reflect its relative importance. Prospective analysts are evaluated based on predetermined criteria, giving a score or grade that reflects their level of suitability to those criteria. Criterion scores are normalized and aggregated to obtain a total score for each candidate analyst. Based on the total score, analyst candidates are ranked, and the Palm Oil Research Center can select the analyst candidate with the highest ranking for acceptance. The application of the COPRAS method in the SPK for accepting analysts at the Palm Oil Research Center is expected to increase the efficiency and accuracy of decision making. This method allows combining subjective preferences and objective information, resulting in more structured and accountable decisions.